2003
DOI: 10.1159/000069176
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Type-2 Diabetes in the Elderly

Abstract: Type-2 diabetes is common in the elderly and when compounded by obesity presents a major challenge for the physician. Obesity plays a central role in the aetiology and pathogenesis of type-2 diabetes. Body weight is determined by an interaction between genetic, environmental and psychosocial factors acting through the physiological mediators of energy intake and expenditure. Obesity is thought to predispose to type-2 diabetes primarily by causing insulin resistance. Education and changes in lifestyle remain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…The current study included patients 60 and older. Similar to other studies, it was found that the content of DSME programs needs to be adapted to older adults with different degrees of independence and comorbidity (Dewan & Wilding, 2013). In addition, it is important for health care providers to ensure that their patients understand key points for diabetes care during their hospital admission regardless of the length of time from diagnosis with diabetes.…”
Section: Discussionsupporting
confidence: 67%
“…The current study included patients 60 and older. Similar to other studies, it was found that the content of DSME programs needs to be adapted to older adults with different degrees of independence and comorbidity (Dewan & Wilding, 2013). In addition, it is important for health care providers to ensure that their patients understand key points for diabetes care during their hospital admission regardless of the length of time from diagnosis with diabetes.…”
Section: Discussionsupporting
confidence: 67%
“…Considerable increased prevalence and earlier age of onset (Ness et al, 1999;Robbins et al, 2000) have been observed in older people (Dewan & Wilding 2003;Selvin et al, 2006), suggesting that genetic factors may influence both timing and prevalence with advance age. Earlier onset of diabetes could also be related to the global epidemic of obesity, leading to the coining of the relatively new term "Diabesity" (diabetes due to obesity).…”
Section: Author (Year)mentioning
confidence: 99%
“…Type I and II diabetes also significantly increases the risk of implant failure 10, 11. The risk to diabetic patients is particularly disconcerting because of the growing incidence of this disease,12, 13 the number of undiagnosed diabetics,12, 13 and the high incidence of type II diabetes in the elderly 12–14…”
Section: Introductionmentioning
confidence: 99%